Case Report: Use of Anakinra in Multisystem Inflammatory Syndrome During COVID-19 Pandemic - Della Paolera, Sara; Valencic, Erica; Piscianz, Elisa; Moressa, Valentina; Tommasini, Alberto; Sagredini, Raffaella; Kiren, Valentina; Comar, Manola; Taddio, Andrea (Frontiers in Pediatrics, 2021)
During COVID-19 outbreak, a large number of children with severe inflammatory disease has been reported. This condition, named Pediatric Multi-inflammatory Syndrome temporally associated with COVID-19 (PIMS-TS) or Multisystem Inflammatory Syndrome associated with Coronavirus Disease 2019 (MIS-C), share some clinical features with Kawasaki disease and is frequently complicated by myocarditis or shock. It has been suggested that MIS-C belongs to the group of cytokine storm syndromes triggered by SARS-CoV-2 infection. So far, intravenous immunoglobulin (IVIG) and systemic glucocorticoids are the most common therapeutic approaches reported in this group of patients. However, the use of anakinra in patients with severe forms of COVID-19 is showing promising results. Here we reported two patients with multisystem inflammatory syndrome complicated with shock. Both the patients presented a poor response to IVIG and systemic glucocorticoids and received anakinra. Treatment with IL-1 receptor antagonist showed a rapid improvement of clinical conditions and biochemical analysis in both patients and demonstrated a good safety profile. Thus, we look forward for future controlled clinical trials with the aim to demonstrate the effectiveness of anakinra in patients with MIS-C and established precise criteria for its use .